THE ROLE OF COMMERCIAL BANKS IN FINANCING SMALL BUSINESSES IN UZBEKISTAN - Sobirovich, Nematulloyev Sukhrob (Antis Publisher, 2024)
This scientific article examines the effective use of investments in the activities of small businesses in our country and the issues of improving the structure of investments involved in this sector. The existing problems are identified and the author's views for solving them are substantiated, and a mechanism for coordinating the interests of investors is developed.